Development of a HIRARC Application for CivilEngineering Occupational Safety and Health - Mohamad Azim Mohammad Azmi,; Shahiron Shahidan,; Mohamad Syamir Senin,; Muhammad Hakimin Mohamad Tahir,; Haziq Adlan Md Hatta,; Mohamad Mahran, Mohamad Arif Haqimi (Multidisciplinary Applied Research and Innovation, 2025)
Development of HIRARC Application for Civil Engineering Occupational Safety and Health aims to address occupational safety and health (OSH) concerns in the construction industry in Malaysia by developing a specifically tailored Hazard Identification, Risk Assessment and RiskControl (HIRARC) application  for civil engineering projects. The objective of this application is to streamline and expedite the process by which users can discern potential risks and hazards in their immediate environment. Ultimately, our application aims to enhance individual preventive measures against identified and latent dangers, contributing to an overall improvement in public safety awareness and proactive risk mitigation. The research will be conducted at University Tun Hussein Onn Malaysia (UTHM) and will involve stakeholder consultation with members of the Occupational Safety and Health (OSH) committee within the UTHM office. Risk and hazard assessment will be limited to the university environment, specifically administrative offices, lecturers' offices, and lecture halls. HIRARC application development will use freely available mobile application development tools and resources, contributing to the cost-effectiveness and accessibility of the project. The project aims to leverage technology and customized approaches to create a safer and more secure environment for construction workers and stakeholders in Malaysia, fostering sustainable growth of the critical construction sector.